Supplying Spin-Offs: Collaboration Practices in the Perpetuation of an Organizaton - Katja Maria Hydle; Kjerst Vikse Meland (Journal of Entrepreneurship, Management and Innovation, 2016)

(untitled)
This paper focuses on the collaboration practices between spin-offs and their customers and suppliers. With empirical material from seven cases of incumbentbacked spin-offs, we find that suppliers are highly involved in the development of the innovation that spin-offs are based upon and specifically, the practices of understanding customers, identifying a market gap and collaborating with suppliers. We contribute to the spin-off literature by revealing which activities are at play for successful spin-offs, and we contribute to practice theory by empirically uncovering the general understandings in the perpetuation of an organization and the nets between the spin-offs and their suppliers.